Orthodontic mini implant, a narrative review - Reginald Iggan, Suzanne Husun; Muhamad Subra, Muhamad Nizam; Ramli, Nor Amlizan; Md Dasor, Maryati (Faculty of Dentistry, Universiti Teknologi MARA, 2025)
The refinement in anchorage management in recent years has magnified the superiority of the mini-implant (MI). Behind the vast clinical literature and low failure rates (Alharbi et al., 2018a), there is a steep learning curve. The lack of updated information on MI focused on understanding the multifactorial success has led to a new area in developing MI research for surface treatment and clinical application. This comprehensive review aims to address the different variables contributing to MI success. The articles were identified electronically (PubMed, Scopus, Google Scholar), ranging from 2018 to date. The articles were independently reviewed by two reviewers (SHR and MMD). Randomised clinical trials (RCT), longitudinal studies, cohort, and case/control studies, both retrospective and prospective, were all included. The following search terms were used: mini-implant orthodontics; mini-implant design; surface treated mini-implant; miniimplant success; mini-implant clinical application; mini-implant The application of MI in orthodontics is bounded by biological factors, geometry, and operational factors. Surface modifications of MI are performed in various ways to increase the primary stability, and the clinical application of MI has expanded in complex cases to mimic surgical correction. The known risks and complications of MI provide sufficient knowledge to negate any problems encountered in clinical situations. It is critical to recognise that MI has its pearls and pitfalls, and we must constantly refine our understanding and clinical applications to maximise the success rate of MI use.